2000
DOI: 10.1115/1.1286601
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Inspection Updating on System Fatigue Reliability of Offshore Structures

Abstract: Offshore structures are considered as fail safe and inspections are carried out during their service lifetime to assess their actual condition. In this paper, the effect of inspection updating on fatigue reliability of offshore structures is investigated. In particular, the effect of inspection on the reliability of both inspected and uninspected joints is assessed dependent upon the correlation of properties of different joints. The effect of repeated inspections and inspection sample size on fatigue reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…These values are in accordance with Moan and Song (2000). Table 1 also lists the value of the PoD parameter (see Equation (14)), which is selected so that the PoD model is representative for magnetic particle inspection; see (Moan et al 2000a).…”
Section: Updating Of the System Collapse Probability With Inspection mentioning
confidence: 93%
See 2 more Smart Citations
“…These values are in accordance with Moan and Song (2000). Table 1 also lists the value of the PoD parameter (see Equation (14)), which is selected so that the PoD model is representative for magnetic particle inspection; see (Moan et al 2000a).…”
Section: Updating Of the System Collapse Probability With Inspection mentioning
confidence: 93%
“…Finally, the correction factors and are fully correlated among all elements. This approach is based on a correlation model suggested in Moan and Song (2000).…”
Section: Statistical Dependence Among Element Fatigue Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The POD curve for an inspection method is obtained from blind-tests or inservice inspection data. In this paper, the PoDs for CVI and MPI are modelled with the commonly-used exponential distribution (Chen et al, 2011, Moan andSong, 2000). The PoD (also the cumulative probability function for variable ) is given by = ( ) = 1 − exp(− ⁄ ) (16) where is the mean detectable crack size.…”
Section: Characterization Of Inspection Methodsmentioning
confidence: 99%
“…Sørensen and Ersdal [23] have shown that a high degree of correlation between the uncertain parameters in different components is needed in order to obtain substantial information which can be used in inspection planning. Moan and Song [24] have studied the influence of inspection updating on the fatigue failure probability of a series system. Uraga and Moan [25] have considered the fatigue reliability of a parallel system consisting of 2 joints.…”
Section: Introductionmentioning
confidence: 99%